ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) PADA PELAKSANAAN BANTUAN SOSIAL COVID-19 DI DINAS SOSIAL PROVINSI DKI JAKARTA - Zulfikar Ali Arafat, (2021)
This research focuses on the application of the government system enforcement system (SPIP) on the implementation of covid-19 social assistance which is realized by implementing elements of internal control according to Government Regulation No. 60 of 2008 on Government Internal Control System (SPIP). Meanwhile, the aim of the researcher in this study is to answer the problem formulation, namely the application of the Government Internal Control System (SPIP) in the implementation of covid-19 social assistance at Dinas Sosial Provinsi DKI Jakarta. This study uses qualitative methods with an interpretive paradigm and ethnometodological approach. The data research technique of this research is by interviewing key information and supporting informants, observation and documentation. The results of this research are the application of SPIP in the implementation of covid-19 social assistance which is running well and adequately, only in the elements of control, information and communication, and monitoring activities, the application of the environmental elements of SPIP in the implementation of covid-19 social assistance has gone quite well , and it is sufficient and the implementation of SPIP risks in the implementation of social assistance has not been going well and is inadequate, due to unidentified distribution schedule problems.